A nonlinear trajectory tracking controller for mobile robots with velocity limitation via parameters regulation. Issue 11 (16th April 2015) - Serrano, Mario E.; Godoy, Sebastián A.; Mut, Vicente A.; Ortiz, Oscar A.; Scaglia, Gustavo J. E.
SUMMARY: This paper addresses the problem of trajectory tracking control in mobile robots under velocity limitations. Following the results reported in ref. [1 ], the problem of trajectory tracking considering control actions constraint is focused and the zero convergence of the tracking errors is demonstrated. In this work, the original methodology is expanded considering a controller that depends not only on the position but also on the velocity. A simple scheme is obtained, which can be easily implemented in others controllers of the literature. Experimental results are presented and discussed, demonstrating the good performance of the controller.